The level of service quality in the Malaysian public service sector - Mohamad Zabri, Mohd Akmal Hakim (International digital organization for scientific information (IDOSI), 2016)
The purpose of this paper is to identify the level of service quality in the Malaysian public service sector.Using a quantitative cross sectional survey approach, a total of 200 self-administered questionnaires were distributed to middle level administrators, regardless of service schemes, in Road Transport Department of Kedah State. Stratified proportionate random sampling technique applied in determining the sampling frame.The data was analyzed using the Statistical Package for Social Sciences (SPSS) version 22 for Windows.Judging from the mean scores, the study suggested that the overall score of training among public servant were of great importance.Finally, implications and some suggestions for future research were also discussed.